The Implementation of Clipping Media in English Learning : A Case Study on Student’s Vocabulary Mastery at Senior High School - Fitriya Ningsih; Fitrah Yuliawati; Arisandi Setiawan (Universitas Islam Negeri Palopo, 2026)
This study aims to determine the implementation of clipping media in English learning to improve vocabulary mastery of class XA students at SMAN 4 Pamekasan. This study used a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation. The results showed that the use of authentic text-based clipping media made a positive contribution to improving students' vocabulary mastery. Students were able to understand the meaning of words through sentence context and showed increased participation during the learning process. In addition, students gave a positive response to the use of clipping media because it made learning more interesting and meaningful. However, there were several obstacles such as differences in student abilities and time constraints. Overall, clipping media can be an effective alternative in improving students' vocabulary mastery.